BUILDING A SMART GREEN CITY: MULTI-ACTOR COLLABORATION IN IoT-BASED FOR WASTE MANAGEMENT - Septina Dwi Rahmawati; Roro Merry Chornelia Wulandary; Radiatul Husni (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The development of modern cities faces increasingly complex challenges, including rapid population growth, rising waste volumes, pollution, and escalating energy demands. Urbanization, higher consumption, and shifting waste generation patterns further complicate waste management. The Smart City concept emphasizes integrating ICT to enhance efficient, inclusive, and sustainable urban governance, while the Green City framework focuses on environmental sustainability within governance. Combining these approaches, the Smart Green City model merges technological innovation with ecological principles, with the Internet of Things (IoT) serving as a key instrument. This study examines the technological dimension alongside sustainability and community well-being. Using a qualitative case study, Malang City was selected for its role as a creative and educational hub in East Java, actively promoting Smart City initiatives with a focus on sustainable environmental management. Implementation challenges include limited budgets, inadequate technological infrastructure, and low community participation. These issues are analysed through major theoretical perspectives to provide a comprehensive understanding of Smart Green City development in Malang, highlighting both the potential and constraints of integrating technology and sustainability in urban planning.